2017
DOI: 10.1177/1469787417721420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of learning design patterns in service learning courses

Abstract: Students participate during service learning courses in a service project, which fits to a community need and has a link to curricular content. Students have a chance while engaged in the service project to apply curricular content in community practice, where they gain insights into civic engagement activities. Empirical studies revealed the effects of service learning, such as its influence on the self-concept, self-efficacy or attitudes to be engaged. However, a lack of research regarding the link between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 24 publications
4
33
1
9
Order By: Relevance
“…It allows students to apply their classroom learning to make a positive change in a community (Huda et al, 2017;Gerholz, Liszt and Klingsieck, 2017;Winterbottom et al, 2015).…”
Section: Matumaini Service-learning Projectmentioning
confidence: 99%
“…It allows students to apply their classroom learning to make a positive change in a community (Huda et al, 2017;Gerholz, Liszt and Klingsieck, 2017;Winterbottom et al, 2015).…”
Section: Matumaini Service-learning Projectmentioning
confidence: 99%
“…Entrepreneurship [25], our study evaluates both the students' self-perception of the benefits of an SL experience for sustainable rural entrepreneurship, covering the curricular, professional, civic and social dimensions, and the possible effect of participation in it on academic success, given the need to gain a better understanding of the global outcomes of SL in terms of training and social transformation [9,10]. Finally, since some researchers have suggested that more rigorous testing is required in order to determine the true effects of SL on university students [8,26], we aim to overcome the main previous statistical limitations regarding sample selection, experimental design, the measurement variables used, and the methodology applied.…”
Section: Sustainability 2019 11 X For Peer Review 3 Of 21mentioning
confidence: 99%
“…Over the last two decades, SL experiences have been linked to increased capacity for understanding theoretical concepts, applying theory to real life, critical thinking, and problem-solving [8,32,33]. SL also builds up students' self-esteem and confidence, as well as their skills in leadership, communication and teamwork [10,34]. Also, working on aspects such as social responsibility, solidarity and sustainability promotes their education in ethical and social values and encourages their citizen participation [1,9,35].…”
Section: University Slmentioning
confidence: 99%
See 2 more Smart Citations